Relating pre-fire canopy species, fire season, and proximity to surface waters to burn severity of boreal wildfires in Alberta, Canada - Rupasinghe PA; Chow-Fraser P (Elsevier, 2021)
Increased global temperature, drought, and extreme weather have increased the frequency and intensity of wildfires in Canadian Boreal forests. We examined how burn severity was related to canopy species composition and proximity to water in six large boreal forest stands across northern Alberta (two in the Bistcho Lake region, three in Wood Buffalo National Park, and one in the Richardson backcountry) and a smaller stand close to the town of Slave Lake (204–5217 km2). We used Landsat 5, 7, and 8 satellite images that included two phenological stages (spring, summer, or fall), followed by Support Vector Machines (SVM) classification to map the distribution of pre-fire canopy species. To quantify the burn severity of each fire, we used the Landsat images to calculate the differenced Normalized Burn Ratio (dNBR); we then combined dNBR for all affected areas to develop the Standardised Burn Impact Score (SBIS), that quantifies the average impact of each fire based on the size of the burned area and mean burn severity per pixel. In general, pre-fire dominance of coniferous species (jack pine and spruce) led to higher SBIS values while pre-fire dominance of broad-leaved species (aspen, birch, and poplar) led to lower values. Mean burn severity and SBIS values increased when fire events occurred at a distance of 1 km or greater from surface waters (e.g. lakes, rivers, and streams). We further analyzed the influence of fire season on burn duration and the proportion of canopy species being burned in each season. We found that fires that were ignited in spring lasted longer and burned more deciduous stands compared to fires that were ignited in summer. By integrating burn impact over very large temporal and spatial scales, we have confirmed the general influence of pre-fire canopy species on burn severity, and the ameliorating effect of surface waters on fire behavior at the landscape level.
Keywords: 4102 Ecological Applications; 41 Environmental Sciences